Pengaruh Self Efficacy terhadap Prokrastinasi Akademik pada Mahasiswa Angkatan 2019 yang sedang Skripsi di Universitas Islam Bandung - Safrina Prasasti Khaerunnisa; Siti Qodariah (Bandung Conference Series: Psychology Science, 2024)
Abstract. Many final year students experience academic procrastination but they feel confident that they can complete their thesis. But in fact, in the class of 2019 students, many students did not do their thesis and delayed working on their thesis so that the thesis did not go right. This is thought to be caused by many factors that arise from students and from the environment around students. Often this happens which has an impact on students becoming less confident about the description being done, often delaying working on the thesis, and feeling less satisfied with the grades obtained. The purpose of this study was to determine the effect of self-efficacy on academic procrastination in students of class 2019 at Bandung Islamic University. The measuring tools used are self-efficacy questionnaires from aspects of Albert Bandura and academic procrastination from Ferrari adapted by Damri.et al (2017). With the validity of 1 item declared invalid, namely statement number 25 on the self-efficacy measurement instrument and reliability test, which is 0.9. This study used a sample of 100 students of class 2019 at Bandung Islamic University. By using accidental sampling techniques, where every student who matches the characteristics of the sample is immediately sampled. The data analysis technique used is Multiple Linear Regression. The research results show that the sig value (0.000 ˂ 0.05) means that Generalization, Level and Strength simultaneously influence academic procrastination. And self-efficacy influences academic procrastination by 51.7%. This means that self-efficacy contributes to academic procrastination. Abstrak. Mahasiswa tingkat akhir banyak yang mengalami prokrastinasi akademik akademik namun mereka merasa yakin dapat menyelesaikan skripsi nya, namun pada kenyataannya pada mahasiswa angkatan 2019 banyak mahasiswa yang tidak mengerjakan skripsi dan menunda mengerjakan skripsi sehingga skripsi tersebut tidak kunjung beres. Banyaknya faktor yang muncul dari diri mahasiswa dan dari lingkungan sekitar mahasiswa, sering memberikan dampak pada mahasiswa menjadi merasa kurang percaya diri terhadap srkripsi yang dikerjakan, sering menunda mengerjakan skripsi, serta merasa kurang puas dengan nilai yang di dapatkan. Tujuannya dilakukan penelitian ini adalah untuk mengetahui pengaruh antara self efficacy terhadap prokrastinasi akademik akademik pada mahasiswa angkatan 2019 di Universitas Islam Bandung. Alat ukur yang digunakan yaitu kuesioner self efficacy dari aspek-aspek Albert Bandura dan prokrastinasi akademik akademik dari Ferrari yang diadaptasi oleh Damri.dkk (2017). Penelitian ini menggunakan sampel 100 mahasiswa angkatan 2019 di Universitas Islam Bandung. Dengan menggunakan Teknik sampling accidental. Teknik analisis data yang digunakan adalah Regresi Linear Berganda. Hasil penelitian menunjukan bahwa nilai sig (0,000 ˂ 0,05) artinya Generalisasi (Generality), Tingkat (Level) dan Kekuatan (Strength) berpengaruh secara bersamaan terhadap prokrastinasi akademik. Dan self efficacy berpengaruh terhadap prokrastinasi akademik Akademik sebesar 51,7%. Artinya self efficacy berkontribusi terhadap prokrastinasi akademik akademik.